LAND GRABBING DAN POTENSI INTERNAL DISPLACEMENT PERSONS (IDP) DALAM MERAUKE INTEGRATED FOOD AND ENERGY ESTATE (MIFEE) DI PAPUA - Tohari, Amin (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
This article discussed the possible impact of land grabbing practice toward the emergence of internal displacement person taken a close look to MIFEE project in papua. employed the concept of acumulation by dispossesion, it was found that the major scale farming development kept a serious impact toward the emergence of internal displacement person. they are ones whose land, forest and other aource of living had been taken away. The MIFEE had cause a socio-cultural gap between farming mechanism and mode of production of the local people, a massice demographical change, economic polarisation, power politics marginalization. with a big number of problems in IDP as a result of dispossesion practice, the IDP is directed toward group that got an effect of development expansion rather than those who suffer from disaster. in the context of human right, the MIFEE was a great potention for the occurance of a violation toward the local people’s right. Keywords: Land Grabbing, Internal Displacement Persons, Accumulation, MIFFEE